Primary production drives ecophysiological cascades in African buffalo - Combrink, Henri, author; Beechler, Brianna, author; Azenwa, Vanessa, author; Jolles, Anna, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
In savannah ecosystems, annual photosynthetic cycles are conspicuous from leaf to landscape level, introducing substantial temporal variability in the quality and quantity of forage plants. As such, the life histories and health of herbivores should be tightly coupled to seasonal phenological patterns; and occurrence patterns of infectious diseases may be driven by the resulting fluctuations in animal immune status. However, few longitudinal datasets including measures of forage quality, along with physiological, immunological and disease outcomes for ungulate consumers have yet been available to test this idea. In this work we used a novel dietary metric, faecal chlorophyll, to show that African buffalo (Syncerus caffer caffer) are highly sensitive to variation in primary production. We demonstrate that faecal chlorophyll correlates tightly with faecal nitrogen, which is often used to evaluate nutritional condition in ungulates; however, faecal chlorophyll assays are far more economical to run. We employ time lagged cross-correlation functions to explore its relationship with various environmental, physiological and immunological parameters and their outcomes for buffalo physiological condition and susceptibility to disease. Our results suggest that primary production is an overwhelming explanatory variable driving broad population level patterns of physiological condition, susceptibility to parasites, disease prevalence and the synergistic outcomes of these on buffalo health. Such strong links to environmental variability have cascading implications for disease dynamics and how we model the spread and maintenance of diseases in ungulate populations. We discuss the implications of this work for evaluating the vulnerability of buffalo to changes in climate, land use or management.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia in conjuction with the IUCN 2nd African Buffalo Symposium.